Detection of Helicobacter suis bacteria in pigs of different age groups - F. M. Nurgaliev (Ветеринария сегодня)
Currently, the pathogenesis of gastric ulcer in pigs remains largely unexplored. The origin of this pathology is most often associated with the type and the technologies of feeding, stresses and disorders of homeostasis of the animal body. The possible involvement of bacteria of the genus Helicobacter in the development of chronic gastritis and gastric ulcer disease in pigs was suggested by the researchers relatively recently. The article comprises the results of investigations aimed at detection of Helicobacter suis bacteria and the contamination degree of porcine gastric mucosa in pigs of different age groups. The stomachs, obtained from suckling pigs, fattening pigs and sows in the slaughterhouse of the Mari El Republic, were examined. The study determined the dependence of pathomorphological changes in the gastric mucosa of pigs on the detection of H. suis in microscopic and biochemical tests as well as in PCR. Thus, no pathomorphological changes in the gastric mucosa of suckling pigs were detected. Severe hyperkeratosis, erosions, and ulcers were found on the stomach mucosa of fattening pigs and sows that were infected with H. suis bacteria. Sows also had ulcerative lesions in the non-glandular region of esophagus. In the biomaterial of suckling piglets the DNA of H. suis bacteria was found only in the pyloric region of the stomach, while in fattening pigs, the DNA of these bacteria was most often isolated from the fundal region, and in sows – from the fundal and cardial regions. This indicates a shift in colonization by helicobacters of the mucous membrane of the stomach from the pyloric to the cardiac sectionincreased with animal age. The obtained research data provide the additional evidence of the etiological role of H. suis in the pathogenesis of gastric ulcer in pigs.